Rated window method and packet size differentiation scheme for TCP fairness in IEEE 802.11 WLAN - Rasul, Tareq (2011)
TCP unfairness issue has becomes pronounced in IEEE 802.11 WLANs due to the distributed coordination function (DCF) mechanism in the 802.11 MAC protocol. It introduces the per-flow and per-station fairness problem between uplink and downlink flows. The uplink flows generally dominate the downlink flows and station with more uplink flows obtains most of the system resources. With the existing of multi-rate capability in WLANs, another performance anomaly of 802.11 can be detected where the performance of a WLAN is determined by the stations with the lowest data transmission rates. The objective of this research is to allocate fair proportional throughput among TCP flows of competing stations in IEEE 802.11 multi-rate infrastructure WLANs by distributing appropriate window and packet size according to the availability of buffer size in the access point (AP). The research scenario focuses on the issue of fairness among stations having different numbers and directions of flow with vary of data transmission rates. In this work, a rated-window size method is performed by proportionally adjust the window size based on transmission rate of each flow. Each of the flow has its own window size and perfectly fit with the portion of available buffer size. Similar with the first method, the second scheme is proposed by manipulating the packet size of each station according to its physical transmission rate so that each station shared proportion bandwidth allocation. The results of total throughput and fairness index are compared with previous methods. Proposed methods generate fair service in terms of proportional throughput among wireless stations. By getting appropriate fairness among each station in accessing WLAN infrastructure, a Wireless Internet Service Provider (WISP) significantly can increase its revenue by providing various service plans that have different service weights and service fees.